Phytochemical investigation among different populations of Papaver bracteatum Lindl. using ultrasonic - assisted extraction method followed by HPLC analysis - Alireza Habibzade; Nasrin Moshtaghi; Saeid Malekzadeh-Shafaroudi (Institue of Medicinal Plants, ACECR, 2021)
Background: Papaver bracteatum Lindl. (Persian poppy) has a very long history as the major source of natural alkaloids. Among Papaver species, Persian poppy can be considered as a rich source of thebaine. Objective: The purpose of this study was to evaluate the thebaine content in different organs and different populations of Persian poppy. Methods: Seven populations of Persian poppy were collected from five different geographical regions of Iran including Damavand (Rineh, Abask), Chalous (Yoush, Pol-e Zanguleh), Mahabad, Meshgin Shahr and Zanjan (Taham) and were screened for its thebaine content. Extraction of thebaine was performed using the ultrasonic-assisted extraction (UAE) method. The parameters including pH, amount of solvent, extraction temperature and time, the repetition of extraction cycles and also the particle size were investigated and optimal conditions were determined to reach the maximum efficiency. Also, the correlation between phenology of the plant and thebaine content was studied during the developmental stages of poppy from pre-flowering to lancing. The developed UAE method followed by high performance liquid chromatography (HPLC) was used for quantitative analysis. Results: Thebaine content was significantly different in various organs and populations grew at different regions. The thebaine content was in the range of 0.9-1.4 % and 0.1-0.45 % in capsules and stems, respectively. The highest thebaine content was obtained in the capsules of Mahabad population. Conclusion: Extraction led to a high purity thebaine from Persian poppy. Eventually, a comprehensive profile of thebaine in different Persian poppy populations from different geographical regions in Iran was released.